Development and usability testing of an online platform for provider training and implementation of cognitive-behavioral therapy guided self-help for eating disorders - Laura D’Adamo; Agatha A. Laboe; Jake Goldberg; Carli P. Howe; Molly Fennig Steinhoff; Bianca DePietro; Marie-Laure Firebaugh; Zafra Cooper; Denise E. Wilfley; Ellen E. Fitzsimmons-Craft (BMC Digital Health)
Abstract Background Most individuals with eating disorders (EDs) do not receive treatment, and those who do receive care typically do not receive evidence-based treatment, partly due to lack of accessible provider training. This study developed a novel “all-in-one” online platform for disseminating training for mental health providers in cognitive-behavioral therapy guided self-help (CBTgsh) for EDs and supporting its implementation. The aim of the study was to obtain usability data from the online platform prior to evaluating its effects on provider training outcomes and patient ED symptom outcomes in an open pilot trial. Methods Nine mental health provider participants (n = 4 in Cycle 1; n = 5 in Cycle 2) and 9 patient participants (n = 4 in Cycle 1; n = 5 in Cycle 2) were enrolled over two cycles of usability testing. In Cycle 1, we recruited providers and patients separately to complete brief platform testing sessions. In Cycle 2, we recruited provider-patient dyads; providers completed training using the platform and subsequently delivered CBTgsh to a patient for three weeks. Usability was assessed using the System Usability Scale (SUS), the Usefulness, Satisfaction, and Ease of Use Questionnaire (USE), and semi-structured interviews. Results Interview feedback converged on two themes for providers (applicability of program for real-world use, platform structure and function) and two themes for patients (barriers and facilitators to engagement, perceived treatment effects). SUS and USE scores were in the “average” to “good” ranges across cycles. Conclusions Findings from this study demonstrate preliminary feasibility and acceptability of the online platform. Data collected in this study will inform further refinements to the online platform. The platform’s effects on provider training outcomes and patient ED symptom outcomes will be evaluated in an open pilot trial. Given the wide treatment gap for EDs and barriers to dissemination and implementation of evidence-based treatments, the online platform represents a scalable solution that could improve access to evidence-based care for EDs.